2019
DOI: 10.2807/1560-7917.es.2019.24.47.1900658
|View full text |Cite
|
Sign up to set email alerts
|

Detection of new endemic focus of tick-borne encephalitis virus (TBEV), Hampshire/Dorset border, England, September 2019

Abstract: The presence of tick-borne encephalitis virus (TBEV) was detected in a questing tick pool in southern England in September 2019. Hitherto, TBEV had only been detected in a limited area in eastern England. This southern English viral genome sequence is distinct from TBEV-UK, being most similar to TBEV-NL. The new location of TBEV presence highlights that the diagnosis of tick-borne encephalitis should be considered in encephalitic patients in areas of the United Kingdom outside eastern England.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 13 publications
1
38
0
Order By: Relevance
“…POWV; (66, 73). The ability to study the evolution of tick-borne viruses is pivotal in our preparedness against these globally emerging pathogens, particularly as evidence for their introduction into new geographic areas continues to be found (2628). Our population genomic study of LIV lays an important foundation for further work and highlights the limitations of estimating viral molecular clock rates in TBFV based on current data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…POWV; (66, 73). The ability to study the evolution of tick-borne viruses is pivotal in our preparedness against these globally emerging pathogens, particularly as evidence for their introduction into new geographic areas continues to be found (2628). Our population genomic study of LIV lays an important foundation for further work and highlights the limitations of estimating viral molecular clock rates in TBFV based on current data.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have reported a recombination event between LIV and TBEV-Eu (19, 23); however, subsequent work has raised doubts about these findings (24). Although the geographic ranges of the two viruses are largely distinct (25), creating limited opportunities for interaction, recent detection of TBEV in Britain (2628), where LIV is endemic, has added new urgency to investigate the possibility of recombination between the two viruses.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades, the incidence of TBE has been fluctuating annually with a general upward trend in several European countries (reviewed in [ 21 ]). Additionally, TBEV and its vectors have invaded novel regions and countries, such as the Netherlands and the United Kingdom, as well as higher altitudes observed in an Austrian alpine region 1500 m above sea level [ 16 , 22 , 23 , 24 , 25 , 26 ]. Possible reasons are a complex interplay of abiotic and biotic factors, combined with socio-economic circumstances and anthropogenic factors [ 26 , 27 , 28 ].…”
Section: Tick-borne Encephalitis Virusmentioning
confidence: 99%
“…Possible reasons are a complex interplay of abiotic and biotic factors, combined with socio-economic circumstances and anthropogenic factors [ 26 , 27 , 28 ]. Furthermore, migratory birds may contribute to an expanded occurrence [ 24 , 29 , 30 ]. In general, TBEV has become an increased international health concern (reviewed in [ 31 ]).…”
Section: Tick-borne Encephalitis Virusmentioning
confidence: 99%
“…This virus is distinct from TBEV-UK-Thetford, but is closely homologous to a TBEV strain identified in the Netherlands, TBEV-NL-Salland, detected in 2017. 2 To date, there have been two autochthonous tick-borne encephalitis cases in the area of the Netherlands where TBEV-NL-Salland was detected. 3 The diversity of the TBEV strains indicates that there have been at least two separate importation events into the UK, possibly via the carriage of infected ticks on migratory birds.…”
Section: Detection Of Tick-borne Encephalitis Virus In the Ukmentioning
confidence: 99%